The ECB's performance under the ESM treaty on a sliding scale of delegation. Issue 3 (19th June 2019) - Lettanie, Ute
Abstract: Two opposing theories explain the European Central Bank's (ECB) far‐reaching powers: principal‐agent and trusteeship. This article situates both theories on a sliding scale of delegation, with agents on one end of the spectrum, and trustees on the other. Applying this new perspective to the European Stability Mechanism (ESM) allows us to understand how the ECB, positioned on the agent side of the scale by the ESM Treaty, slides towards the trustee side in practice. This way, the article identifies two problems. Firstly, the ECB assumes a 'zone of discretion' that is not captured by the control mechanisms, thereby disregarding an essential feature of delegation. Secondly, the rationale of the Meroni doctrine, judicial review, is disregarded given the insufficient protection against the ECB's actions. These findings become increasingly important with the long‐term aim to incorporate the ESM in the EU legal order.